The Effect of Music Therapy on Aggression Levels in Schizophrenic Patients - Retno Pawistiyatun; Apriana Rahmawati; Tri Mustikowati; Suharpudianto Suharpudianto (GLOBAL HEALTH SCIENCE GROUP, 2025)
This study aims to determine the effect of music therapy on the level of aggression in schizophrenia patients. The research method used was quasi-experimental with one group pre-test and post-test design. A total of 25 respondents were selected using accidental sampling techniques. The intervention was given in four music therapy sessions with a gradual duration of between 30 to 45 minutes per session. The level of aggression was measured using the Buss and Perry Aggression Questionnaire. The Relationship Between Cognitive Function and Aggression in Schizophrenia Patients (Indonesia, 2023). This study was conducted at Ernaldi Bahar Hospital in Palembang and used the BPAQ to measure aggression and the MoCA-Ina to assess cognitive function. The results showed a significant negative relationship between cognitive function and aggression (p = 0.04; r = -0.340), meaning that a decline in cognitive function is associated with increased aggression in schizophrenia patients. Multivariate analysis showed that cognitive function scores influenced aggression scores (R² = 0.207; β = -0.730; p = 0.005).The results of the analysis showed a significant decrease in aggression levels after the administration of music therapy. A statistical test using the Wilcoxon Test yielded a P-value of < 0.001, which indicates that music therapy has a significant effect on reducing aggression levels in schizophrenic patients.